Penerapan Terapi Senam Otak Terhadap Fungsi Kognitif Pada Pralansia Di Desa Bororejo Kelurahan Jagalan - Nurico Irhamna Arlansyah; Irma Mustika Sari (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Background: Midleage is a process that all humans will experience, a process that will be marked by memory impairment, understanding and concentration. That decline is commonly referred to asa decline in cognitive function. It's a therapeutic technique that gives the brain a stimulus to increase cognitive function so as to maintain memory function, a concentration of learning and understanding memory. Purpose: describe improvements seen after and before, improvements and comparative cognitive function. Method: this study is a therapeutic study with case studies using a descriptive method. Results: the study shows that prior to her cerebral palsy, Mrs. V and Mrs. V. The same "s" has a mild cognitive decline, after five brain calist-therapy meetings in five weeks and 15 minutes both respondents have increased cognitive function to normal. Conclusion: cerebral exercise can increase cognitive function in Midleage in the village of Bororejo.